The role of sports marketing in increasing the marketing value of a football player - Al-Zarfi, Asst. L. Hussein Ali Abdul Yasser (Sulaimani Journal for Humanities, 2025)
This study aimed to explore the relationship between the strategic use of social media platforms and the market value of football players, with the goal of enhancing their online presence and marketability. A player's online presence encompasses various aspects, including television appearances, social media presence, and fan engagement. This engagement is a crucial factor in the sponsorship and support a player receives and is an important element in financial valuation. This multidimensional impact will be examined in several aspects. 1. The following section will address followers and engagement. A strong correlation has been established between a player's number of social media followers and their market value, with higher follower counts leading to increased visibility and commercial opportunities. 2. Performance Enhancement: The link between goals scored, social media activity, and player performance warrants further investigation. 3. Attention Economy: Players are brands competing for public attention, and their ability to attract an audience is reflected in their marketability and revenue. Current findings indicate that commercial partnerships and sponsorships are associated with increased social media visibility. An athlete's role as a brand ambassador is amplified through social media, while their market value increases through endorsements. Strategic use of social media has proven to enhance the market value of players on the field. However, this phenomenon is not without its challenges, particularly the pressure to maintain a certain image and level of publicity, which, in the event of negative results, can lead to frustration and diminish the player's true value.
Keywords: Sports marketing; football